Exploring the Interplay of AHD, TB, and Cryptococcal Antigen in Nasarawa State (London Journal of Medical and Health Research, 2023)
This study explored the existing relationships between Advanced HIV Disease (AHD), Tuberculosis (TB), and Cryptococcal Antigen (CrAg) among People Living with HIV (PLHIV) in Nasarawa State, Nigeria. This was achieved by investigating the relationship and prevalence of TB and CrAg among individuals diagnosed with AHD in Nasarawa State; and by assessing the distribution and association of demographic characteristics of the study population with TB and Cryptococcal Antigen. This study employed a cross-sectional survey design, sampling respon-dents across different demographics at the same time. The study sample were individuals who are currently receiving antiretroviral treatment from six healthcare facilities in Nasarawa State, Nigeria. Results showed that TB and CrAg has low prevalence among the study population, however, compared to a larger population, this will be a serious concern. The study also suggests that the demographic information of the study population had no significant relationship on the development or presence of TB or CrAg, however, the study was able to establish that PLHIVs who had AHD were mostly women (59.8%) in the State. Recommendations were made based on the study findings and the study concluded that the existing relationships among the study variables were not impacted significantly by either age or gender of the population.
Keywords: antimicrobial resistant infections; 75-% dosages of MSAMS-stabilized medicines; antioxidant-supportive treatments.; advanced HIV disease (AHD); cryptococcal antigen (CrAg); people living with HIV (PLHIV); human immunodeficiency virus (HIV).